2011
DOI: 10.2217/clp.11.11
|View full text |Cite
|
Sign up to set email alerts
|

Associations of BMI and its fat-free and fat components with blood lipids in children: Project HeartBeat!

Abstract: Aim This study aimed to distinguish between the roles of the two components of BMI, the fat mass (FM) index and the fat-free mass (FFM) index, in BMI’s association with blood lipids in children and adolescents. Methods A total of 678 children (49.1% female, 79.9% non-black), initially aged 8, 11 and 14 years, were followed at 4-month intervals for up to 4 years (1991–1995). Total cholesterol (TC), LDL-C, HDL-C and triglycerides were determined in fasting blood samples. FFM index and FM index were calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…For example, its use as a surrogate of percent body fat (%BF) has been deemed inappropriate for normal‐weight children ; of low sensitivity ; and while appropriate for general screening, it was considered unsuitable for individual diagnosis . On the other hand, its involvement in pediatric studies has been supported on the basis of its ease of measurement, its significant moderate associations with %BF , the satisfactory sensitivity and specificity of BMI‐based obesity classifications when adjusted for age and sex , and its associations with cardiovascular risk factors in adolescents and children .…”
Section: Introductionmentioning
confidence: 99%
“…For example, its use as a surrogate of percent body fat (%BF) has been deemed inappropriate for normal‐weight children ; of low sensitivity ; and while appropriate for general screening, it was considered unsuitable for individual diagnosis . On the other hand, its involvement in pediatric studies has been supported on the basis of its ease of measurement, its significant moderate associations with %BF , the satisfactory sensitivity and specificity of BMI‐based obesity classifications when adjusted for age and sex , and its associations with cardiovascular risk factors in adolescents and children .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in obese children, Weber et al [32] found that higher lean mass was associated with increased odds of abnormal BP, HDL cholesterol, and WC, even after adjustment for fat mass. Another smaller study [33] found similar associations between higher lean mass and cardiometabolic risk factors (reviewed in (15).…”
Section: Discussionmentioning
confidence: 69%
“…Overweight or obese children are prone to dyslipidaemia, and previous studies have reported that there is a positive association between BMI and TG in adults and children [35][36][37] . However, our study did not nd a relationship between BMI and TG in children and adolescents with short stature.…”
Section: Discussionmentioning
confidence: 99%